The effects of long-term prenatal exposure to 900, 1800, and 2100 MHz electromagnetic field radiation on myocardial tissue of rats - AKAKIN, DİLEK (My University, 2022)
It is well-known that wireless communication technologies facilitate human life. However, the harmful effects of electromagnetic field (EMF) radiation on the human body should not be ignored. In the present study, we evaluated the effects of long-term, prenatal exposure to EMF radiation on the myocardium of rats at varying durations. Overall, 18 pregnant Sprague-Dawley rats were assigned into six groups (n = 3 in each group). In all groups other than the control group, three pregnant rats were exposed to EMF radiation (900, 1800 and 2100 MHz) for 6, 12 and 24 h over 20 days. After delivery, the newborn male pups were identified and six newborn male pups from each group were randomly selected. Then, histopathological and biochemical analysis of myocardial samples were performed. When 24-h/day prenatal exposures to 900, 1800, 2100 MHz EMF radiation were evaluated, myocardial damage was greater in the 2100 MHz EMF-24h group than the other groups. In addition, when malondialdehyde (MDA) and glutathione (GSH) levels associated with reactive oxidative species (ROS) were evaluated, the MDA level was higher in the 2100 MHz EMF-24h group compared with the other groups. The GSH level was also lower in the 2100 MHz EMF-24h group. When the 6, 12 and 24 h/day prenatal exposures to 1800 MHz EMF radiation were evaluated, myocardial damage was greater in 1800 MHz EMF-24h group than the remaining groups (p < 0.0001). Also, MDA level was greater in the 1800 MHz EMF-24h group compared with the other groups while the GSH level was lower in this group. It was shown that myocardial tissue was affected more by long-term exposure to EMF radiation at high frequencies. The data raise concerns that the harmful effects of non-ionizing radiation exposure on cardiac tissue will increase with 5G technology.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Social Sciences and Humanities; Sociology; Life Sciences; Health Sciences; Natural Sciences; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); TOKSİKOLOJİ; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); TOXICOLOGY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); İş Sağlığı ve Terapisi; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Toksikoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Sağlık, Toksikoloji ve Mutajenez; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Safety Research; Health (social science); General Social Sciences; Toxicology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Public Health, Environmental and Occupational Health; Epidemiology; Health, Toxicology and Mutagenesis; Physical Sciences; Social Sciences & Humanities; electromagnetic field radiation; electromagnetic wave; exposure; myocardial; prenatal; RADIOFREQUENCY RADIATION; STRESS